(untitled) (Journal of Mathematical Study, 2024)
In this paper, we establish the endpoint estimate for an oscillatory multiplier associated with wave equations on the torus, which extends the results of Fan and Sun. In addition, we obtain a more general result for sublinear operators on compact measure spaces.